Tingkat Kebugaran Jasmani Siswa Sekolah Dasar Negeri 1 Bumirejo - Ibnu Prasetyo Widiyono; Miftakhurrohman Miftakhurrohman (Journal on Education, 2024)
This research aims to determine the level of physical fitness of male and female students at SD Negeri 1 Bumirejo. This research is a descriptive study which will later be revealed to describe the physical condition (VO2Max) of students at SD Negeri 1 Bumirejo. The sampling technique used total sampling, the number of students who took part was 20 participants. The instrument used in this research is the bleep test. The data analysis technique uses descriptive analysis in the implementation of sports measurement tests that measure the VO2Max level of students at SD Negeri 1 Bumirejo. From the results of the research and discussion, it can be concluded that the results of the bleep test show that the students' overall level of endurance still has a low rating. It can be seen from the results obtained that the lowest result is 20.8 and the highest score in this test is 44.5. From these gains, it is necessary to carry out more supervision and increase physical training in order to improve students' physical fitness.